2002
DOI: 10.1074/jbc.m203318200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Family of Oxidized Phospholipids That Serve as Ligands for the Macrophage Scavenger Receptor CD36

Abstract: The macrophage scavenger receptor CD36 plays an important role in the uptake of oxidized forms of low density lipoprotein (LDL) and contributes to lesion development in murine models of atherosclerosis. However, the structural basis of CD36 lipoprotein ligand recognition is unknown. We now identify a novel class of oxidized phospholipids that serve as high affinity ligands for CD36 and mediate recognition of oxidized forms of LDL by CD36 on macrophages. Small unilamellar vesicles of homogeneous phosphatidylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
472
0
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 421 publications
(486 citation statements)
references
References 63 publications
7
472
0
7
Order By: Relevance
“…In terms of modified LDL, the exact nature of the CD36 ligand has been recently defined as a truncated phosphatidylcholine species, with a specific sn-2 esterified γ-hydroxy (or oxo) -α,β-unsaturated carbonyl containing fatty acid (Podrez, et al, 2002a,Podrez, et al, 2002b. These modifications can occur as a result of the action of reactive oxygen or nitrogen species.…”
Section: Cd36 Ligands and Functionsmentioning
confidence: 99%
“…In terms of modified LDL, the exact nature of the CD36 ligand has been recently defined as a truncated phosphatidylcholine species, with a specific sn-2 esterified γ-hydroxy (or oxo) -α,β-unsaturated carbonyl containing fatty acid (Podrez, et al, 2002a,Podrez, et al, 2002b. These modifications can occur as a result of the action of reactive oxygen or nitrogen species.…”
Section: Cd36 Ligands and Functionsmentioning
confidence: 99%
“…[12][13][14] Cellular uptake of oxLDL is mediated by the binding of oxidized phosphatidylcholine (oxPC) molecules, the principal oxidized phospholipid present in oxLDL, to scavenger receptors. 15,16 Recently, a specific monoclonal antibody against oxPC was developed by one of us. 17,18 Using this antibody, we have investigated the influence of oxidative stress on various diseases.…”
mentioning
confidence: 99%
“…The structures of oxPC CD36 identified were established using a combination of cell binding studies and multiple distinct chromatographic and MS methods in conjunction with (i) results of numerous derivatization strategies to ascertain functional groups on isolated products, (ii) inference of structures of products that appeared plausible based upon MS results and known mechanisms of lipid oxidation and fragmentation, and (iii) de novo synthesis of each oxidized lipid. The identities of the oxidation products and synthetic standards were confirmed by demonstration that synthetic species recapitulate all biological, chemical, MS, and chromatographic characteristics of the lipids isolated from oxidized 1-palmitoyl-2-arachidonyl-sn-glycero-3-PC, oxidized 1-palmitoyl-2-lineoyl-sn-glycero-3-PC, and oxidized 1-palmitoyl-2-docosahexaenoyl-sn-glycero-3-PC (19,20,22,40,41). Liquid chromatographic/electrospray ionization/tandem MS analyses have demonstrated the generation of these species in lipoproteins oxidized by multiple distinct pathways in vitro (40), in atherosclerotic lesions in vivo (41), in retina following light exposure in dark-adapted rodents (20), and in cerebral tissues following ischemia-reperfusion injury (42).…”
Section: Structural Characterization Of Oxpc That Serves As a High Afmentioning
confidence: 94%
“…Although initially defined using PC molecular species, as outlined below, subsequent studies have shown that all classes of phospholipids examined thus far (PC, phosphatidylethanolamine, PS, and phosphatidic acid) harboring the high affinity motif for CD36 promote CD36-mediated recognition and phagocytosis (19,20,22,40,41). The structures of oxPC CD36 identified were established using a combination of cell binding studies and multiple distinct chromatographic and MS methods in conjunction with (i) results of numerous derivatization strategies to ascertain functional groups on isolated products, (ii) inference of structures of products that appeared plausible based upon MS results and known mechanisms of lipid oxidation and fragmentation, and (iii) de novo synthesis of each oxidized lipid.…”
Section: Structural Characterization Of Oxpc That Serves As a High Afmentioning
confidence: 99%
See 1 more Smart Citation